East Indian Family, Trinidad, B.W.I. - (:unkn) unknown (Photogelatine Engraving Co. Limited, Ottawa, 2008)
Three Members of an East Indian Family. Attached 4 cents Trinidad and Tobago Postage stamp dated 22 May 1907. Postcard numbered 20809.
Colour: Yellow and White; Style: Landscape; Other: Bordered, Divided
Keywords: Postcards; East Indians--Trinidad and Tobago; 1907; Families--Trinidad and Tobago; Trinidad and Tobago; Huts--Trinidad and Tobago; Jewelry--Indian